Microbial fuel cell: optimizing pH of anolyte and catholyte by using taguchi method. Issue 1 (18th September 2016) - Kumar, Pradeep; Mungray, Arvind Kumar
Abstract : In this study, the Taguchi method was used to optimize pH of anolyte and catholyte in terms of obtaining maximum power density of a microbial fuel cell (MFC). The anolyte pH and catholyte pH were selected as operating parameters, with their corresponding levels. L16 orthogonal array was selected for the experimental design. Each of experiments was repeated two times for calculating the signal‐to‐noise (S/N) ratio. However, based on Taguchi method, optimum anolyte and catholyte pH were observed 8 and 1, respectively. A confirmation experiment was done with the optimum conditions and based on that, maximum power density was observed at 2491.42 mW/m 3 . Analysis of variance (ANOVA) was carried to recognize the percentage contributions of operating parameters in the process and accordingly it was found 53.59% for anolyte and 46.40% for catholyte pH. The optimization study of both pH suggests low internal resistances and high Coulombic efficiency that favored for both high power density. © 2016 American Institute of Chemical Engineers Environ Prog, 36: 120–128, 2017